2020
DOI: 10.2298/sos2004445k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aging processes on tribo-metallurgy properties of al based ternary alloys product by P/M technique

Abstract: In this study, Al matrix composites consisting of different amounts of Zn, Cu, and Mg were produced using the powder metallurgy technique. In the alloying, powders were ball milled for 120 min via mechanical alloying. After alloying process, the powders were pressed at 800 MPa at room temperature. Sintering (2 h at 600?C in argon atmosphere), solution treatment (2 h at 480?C), and aging processes (3, 6, 9, and 12 h, respectively, at 120?C) were applied to the samples. The hardness and trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Besides, it allows the production of small, functional, incompatible, difficult-to-manufacture parts with low dimensional tolerance [3], so it is possible to fabricate parts that are ready for direct usage. Also, it is possible to prepare various steel alloys and modify the chemical composition of the materials with precision [4,5]. Therefore, P/M steels have been utilized to fabricate structural parts in the mechanical fields and automotive industry [6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it allows the production of small, functional, incompatible, difficult-to-manufacture parts with low dimensional tolerance [3], so it is possible to fabricate parts that are ready for direct usage. Also, it is possible to prepare various steel alloys and modify the chemical composition of the materials with precision [4,5]. Therefore, P/M steels have been utilized to fabricate structural parts in the mechanical fields and automotive industry [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another important parameter for characterizing the wear behavior is the friction coefficient. The coefficient of friction (CoF) provides significant information about the tribological behavior of the sample [25]. The CoF values obtained during the wear tests under 15 N load are given in Fig.…”
Section: Wear Characteristics Of Heat-treated Aisi H13 Steelmentioning
confidence: 99%
“…The parts produced by this method have a less rough surface than the parts produced by other methods and often do not require secondary processing. Homogeneous distribution of the quality, completely controllable ingredient and content, and low unit cost make powder metallurgy as a unique production method in the production industry [8][9][10][11][12][13]. Thus, it was found that approximately 97 % of the material was used in mass production with PM.…”
Section: Introductionmentioning
confidence: 99%